Successful bridge to lung transplantation with transcatheter aortic valve replacement. Issue 12 (19th July 2020) - Wallen, Tyler J.; Arnaoutakis, George J.; Beaver, Thomas; Pelaez, Andres; Chandrashekaran, Satish; Shahmohammadi, Abbas; Emtiazjoo, Amir M.; Spiess, Bruce; Pipkin, Mauricio; Machuca, Tiago N.
Abstract : End‐stage lung disease and advanced cardiac conditions are frequently seen together and represent a clinical dilemma. Even though both issues may be amenable to surgical management, combining lung transplant with surgical valve repair is rarely done and theoretically associated with increased morbidity and mortality risks, especially in elderly patients. Here, we describe 2 patients presenting with end‐stage lung disease and significant aortic stenosis who were successfully bridged to lung transplant via transcatheter aortic valve replacement. Patient 1 was a 66‐year‐old man who underwent a double lung transplant 56 days after transcatheter aortic valve replacement. Patient 2 was a 70‐year‐old man who underwent a single right lung transplant 103 days after transcatheter aortic valve replacement. Both patients had uneventful postoperative courses and are alive at the 1‐year time point with excellent performance status. This report suggests that transcatheter aortic valve replacement may favorably impact lung transplant candidacy for patients with end‐stage lung disease in the setting of severe aortic stenosis, likely representing a better alternative to concomitant aortic valve replacement and lung transplant in elderly patients. Abstract : Transcatheter aortic valve replacement used to treat aortic stenosis in two patients with end‐stage lung disease leads to favorable impact on lung transplant candidacy.